Geophysical search of library of Ivan IV - V Yur'evich Abramov; V Ivanovich Brovkin; V I Pyatnitsky (RUDN Journal of Engineering Research, 2011)
Enthusiast group (engineer, geologist, archeologist) make a search a Russian tsar Ivan library. Present a result from frequency and radiowave sounding an Dijakov Church.